Breast-conserving surgery is an appropriate procedure for centrally located breast cancer: a population-based retrospective cohort study - Ye-Wei Yuan; Peng-Cheng Liu; Fang-Fang Li; Ya-Han Yang; Wei Yang; Li Fan; De-Wu Mou; Hong-Wei Yang; Mao-Shan Chen (BMC Surgery, 2023)
Abstract Background The evidence of breast-conserving therapy (BCT) applied in centrally located breast cancer (CLBC) is absent. This study aims to investigate the long-term survival of breast-conserving therapy (BCT) in centrally located breast cancer (CLBC) compared with mastectomy in CLBC and BCT in non-CLBC. Methods Two hundred ten thousand four hundred nine women with unilateral T1-2 breast cancer undergoing BCT or mastectomy were identified from the Surveillance, Epidemiology, and End Results database. Kaplan–Meier survival curves were assessed via log-rank test. Propensity score matching (PSM) was used to balance baseline features, and the multivariable Cox model was used to estimate the adjusted hazard ratio [HR] and its 95% confidence interval [CI] for breast cancer-specific survival (BCSS) and overall survival (OS). Results With a median follow-up of 91 months, the BCSS and OS rates in patients who received BCT were greater than those patients treated with mastectomy in the entire CLBC set. Multivariable Cox analyses showed that CLBC patients who received BCT had better BCSS (HR = 0.67, 95%CI: 0.55–0.80, p < 0.001) and OS (HR = 0.78, 95%CI: 0.68–0.90, p = 0.001) than patients who received a mastectomy, but there were no significant differences of BCSS (HR = 0.65, 95%CI: 0.47–0.90, p = 0.009) and OS (HR = 0.82, 95%CI: 0.65–1.04, p = 0.110) after PSM. In patients treated with BCT, CLBC patients had a similar BCSS (HR = 0.99, 95%CI: 0.87–1.12, p = 0.850) but a worse OS (HR = 1.09, 95%CI: 1.01–1.18, p = 0.040) compared to that of the non-CLBC patient, but there was no significant difference both BCSS (HR = 1.05, 95%CI: 0.88–1.24, p = 0.614) and OS (HR = 1.08, 95%CI: 0.97–1.20, p = 0.168) after PSM. Conclusion Our findings revealed that BCT should be an acceptable and preferable alternative to mastectomy for well-selected patients with CLBC.